Kształtowanie się celów politycznych dyplomacji księcia Adama Jerzego Czartoryskiego wobec Wielkiej Brytanii (1831/1832) - Żurawski vel Grajewski, Radosław (Acta Universitatis Lodziensis. Folia Historica, 1995)
The diplomatic action of A. J. Czartoryski’s camp in Great Britain in the first months of emigration was the direct continuation of the works carried on during the November Uprising. Until the Prince’s arrival in London on 22 December 1831, the Polish side was represented by Julian Ursyn Niemcewicz and Alexander Walewski. Then the Prince carried on the action himself. Till the mid January 1832 the attitude of the Polish side and the political aims of its activities underwent considerable evolution. At frequent meetings the British politicians (Grey, Palmerstone and Brougham) were presented with many memorials concerning the Polish question and the possibility of obtaining the English support on international forum was discussed. At first they tried to persuade the British to the Polish interpretation of the resolutions of The Vienna Treaty which Prince Czartoryski perceived as an international legal base for the intervention of the western empires on the benefit of Poland. To stress the separate character of the Polish Kingdom and Russia they tried to send the British consul to Warszawa. They expected from the British diplomacy activities aiming at mitigation of the Russian repressions, preserving constitutional privillages in the Kingdom and introducing national institutions in the former Polish gubernyas of the Russian Empire. At the initial period they resigned from defending the postulate of full Polish independence. Only at the end of December 1831 and in January 1832 they attempted to arouse Great Britain’s interest in the idea of rebuilding fully independent Poland, to achieve the French-English rapprochement and to create the united front of these empires against Russia. They set forth the postulate of uniting the Polish gubernyas of the empire with the Kingdom and they even probed the possibility of military engagement of England and France against Russia. In the second half of January a rapid retreat took place: from the active shaping of situation in Poland for the benefit of defending already achieved advantages and preserving the status of the Polish Kingdom. The main task of the Polish diplomacy was restraining Great Britain from recognition of constitutional changes carried on by the Russians and creating the conviction that in the light of international law those changes were illegal. During the whole discussed period they stressed the advantages that Great Britain and Europe might have if independent Poland had been created, especially if it were treated as anti-Russian barrier. The British diplomacy quite quickly accepted the Polish interpretation of the Vienna Treaty, but the impassable barrier of their involvement in supporting the Polish case was the direct military intervention which England did not want and could not take up and without which there were only limited possibilities of having influence on the Russian actions in Poland. Finally, the positive result of Czartoryski’s action was preserving the presence of the Polish question on international arena, disturbing its the unfavourable closing and treating it as Russia’s own home affair.